Pemanfaatan Kawasan Banten Lama Pemanfaatan Kawasan Banten Lama Sebagai Sumber Pembelajaran IPS di SD Labschool UPI Kampus Serang Berbasis Aplikasi Powtoon: Untuk Menguatkan Profil Pelajar Pancasila - Supriatna, Encep; Susi, Susilawati; Ita, Ita Rustiati Ridwan (Journal of Mandalika Literature, 2025)
Abstract: So far, social studies learning has tended to be rote, and teachers present facts from the past, without the help of adequate media. In the era of digital technology, there are actually many applications that teachers can use to convey material in class to make learning social studies/science more interesting. The aim of the research is to determine the potential of the Old Banten Historical Site as a social studies learning resource based on the Powtoon application for elementary school students at SD Labschool UPI Serang Campus, Serang City, Banten. Powtoon is a simple to use web-based application that can be used to create animated videos attractively and quickly. The research was carried out using the R & D method from February 2024 to September 2024. Bearing in mind the importance of digital literacy skills for a teacher to be creative in teaching in the classroom. Animated Video Based on the Powtoon Application on the theme of Indonesia's rich culture in the fourth grade of elementary school, such as the uniqueness and customs of the people around me, the richness of Indonesian culture, as well as the benefits of diversity and preserving cultural diversity. In addition, the use of technology in learning media can stimulate students' interest and motivation to learn about social studies. One of them is the Indonesian Cultural Diversity animation video about the customs of the people around me and the richness of Indonesian culture, which can strengthen students as a way to strengthen the student profile of Pancasila, especially the Global Diversity component. The research method uses the Hannafin & Peck R & D Model which consists of three phases, namely Needs analysis, design, development and Implementation, all three of which involve evaluation and revision stages. Various historical relics were made into learning videos using the Powtoon application and used in the learning process at the Labschool UPI Elementary School, Campus Serang, as an effort to strengthen the profile of Pancasila students, especially in the aspect of global diversity.